Answer to Question #10663 in Abstract Algebra for Manthan khorwal
& 1. 3x3-2x2-7x-2 By substituting x=-1 we find out that it's a root. So we divide& 3x3-2x2-7x-2 by x+1 We obtain 3x2-5x-2 Therefore 3x3-2x2-7x-2=(x+1)(3x2-5x-2) Let's find roots of 3x2-5x-2 D=25+2*4*3=25+24=49 x=(5+7)/6=2 x=(5-7)/6=-1/3 Finally we get 3x3-2x2-7x-2=3(x+1)(x-2)(x+1/3)
Going back to school after summer vacation is not the easiest thing to do. In fact, it takes more mental…
APPROVED BY CLIENTS
AssignmentExpert has been a life saver!! I was very skeptical at first but I didn't have any other options so I tried them out and would HIGHLY recommend them to everyone!!!!! I made a A in Statistics thanks to AssignmentExpert!!!